Kim jest postmodernistyczny "homo oeconomicus", czyli pytanie o współczesne relacje pomiędzy rodziną a rynkiem - Michalski, Michał Adam (Annales. Etyka w Życiu Gospodarczym, 2011)
This article undertakes the question of „economic man” in context of postmodern philosophy. The purpose of it is to analyze currentunderstanding of man in market surrounding and his family relations.In the beginning the genesis of homo economicus model is presented and attempt is made to find answer to the question of itscontemporary meaning and “family situation”. Then the article shows why we should resign from using this model and substitute it withhomo socioeconomicus.The very concept of homo economicus – well known and often discussed – although reduces human being, in the light of postmodernthinking seems to relive. That is why it is necessary to reflect if there is similarity between “economic man” and the vision of man preferredby postmodernism. One of the proofs for it may be current situation of family which is not supported by postmodern homo economicusconcept. It seems to be logical consequence when we realize that individualism of “economic man” is strengthened by postmodern antipathytowards social institutions.